Characteristics of earthquake ground motions and the H - Huang, Huey Chu
The relationships between the spectral characteristics of earthquake ground motions and those of microtremors are investigated using the observed data from a dense strong motion network consisting of 108 stations in the Yun-Li, Chia-Yi and Tai-Nan areas in southwestern Taiwan. Many high quality recordings, including those of the 921 Chi Chi earthquake (Mw=7.6), the 1022 Chia-Yi mainshock (ML=6.4), the 1022 major aftershock (ML=6.0), as well as some weak motion events are selected to evaluate site responses. Microtremor measurements are also performed at most ground motion stations. With many stations in the area located on an alluvium structure, however, it is difficult to find good reference stations on rock sites, which therefore necessitates the calculation of single station H/V ratios. The predominant frequencies obtained from H/V ratios are consistent with those from spectral ratios. The site characteristics between the strong and weak events are different, however. This implies that a nonlinear effect probably occured with the strong motion events. The main peak in the H/V spectra of the microtremors is in good agreement with the first peak obtained from the spectra of earthquake ground motions. It is reasonable to claim that the main peak reflects the deep underground structure. On the basis of the H/V ratios of the microtremors, it is concluded that the lower predominant frequencies appear in the plain area, while the higher values are near the mountainous region.
Keywords: Microtremor; The Chi Chi earthquake; Site response; H/V ratio; Predominant frequency; Nonlinear effect